GRP-137 Pharmaceutical Interventions at Beatriz Angelo Hospital. (12th March 2013) - Marques, E; Capoulas, M; França, L; Pereira, N; Castro, S; Santos, P; Figueiredo, R; Neves, A; Santos, C; Fernandez-Llimós, F
Abstract : Background: Beatriz Ângelo Hospital (HBA) is 424-bed district hospital (210-bed Medical Specialties, 90-bed Surgical Specialties, and 22-bed Intensive/Intermediate care unit, among others). All prescriptions are validated by a pharmacist at the Department of Pharmacy (DP), and it is always possible to access the electronic medical record of each patient to consult clinical data and record any suggestions or interventions. For the purposes of this study, pharmaceutical interventions (PIs) are defined as contact with other healthcare providers in order to prevent any medicines-related problems (MRPs). Purpose: To quantify and characterise PIs at HBA following the identification of any risks of MRPs during prescription validation. Materials and Methods: Prospective data collection from 1 July to 30 September and subsequent entering of the data into a PIs database created by the HBA's DP according to a protocol developed by the DP of Hospital da Luz and Faculdade de Farmácia da Universidade de Lisboa. Results: During the period of analysis, 914 PIs were recorded for a total of 280 patients (an average of 3.3 PIs per patient), with the following distribution: 242 PIs in Intensive Care units, 400 in the Medical Specialties, 214 in the Surgical Specialties and 58 in other units. The most frequent causes of PIs were: unsuitable use of medicine due to the renal function (n = 420 [46.0%]); potential adverse effect/toxicity (n = 139 [15.2%]); and lack of therapeutic efficacy (n = 112 [12.3%]). The most frequent PIs were therapeutic drug monitoring (n = 343 [37.5%]); suggestions regarding parameters found in blood tests (n = 241 [26.4%]); adjustments to dose and frequency of administration (n = 106 [11.6%]); adjustments to route of administration and medicine formulation (n = 07 [11.7%]). As for the expected effects of PI, the most frequent were: increased effectiveness (n = 548 [60.0%]); reduced drug toxicity (n = 205 [22.4%]); reduced risk associated with route of administration (n = 104 [11.4%]). Concerning the results of PI, the most frequent were: no clinical improvement/no clinical aggravation (n = 289 [31.6%]); problem prevented (n = 248 [27.1%]); clinical improvement (n = 238 [26.0%]). Of all PIs, 813 (88.9%) were accepted, and 328 (35.9%) of all PIs were recorded in the patient's electronic medical record. Conclusions: The high acceptance of PIs confirms the interdisciplinary cooperation of all the healthcare providers within the institution. The results show that PI is fundamental in promoting the good use of medicines and preventing MRPs. The development of a software application integrated in the electronic medical record will allow us to be more agile in documentation and to quantify the pharmacist's contribution within the clinical team. No conflict of interest.